An incidental case of gastric pseudomyiasis in Canis latrans (Carnivora: Canidae) by a rabbit bot fly Cuterebra sp. (Diptera: Oestridae) - Nora Lara-Lagunes; Santiago Jaume-Schinkel; Sergio Ibáñez-Bernal (Revista Mexicana de Biodiversidad)
An incidental case of gastric pseudomyiasis in the coyote Canis latrans by a rabbit bot fly Cuterebra sp. is documented. In a coyote scat not entirely solid but somewhat watery and surrounded by mucous in the municipality of Perote, state of Veracruz, 2 myiasigenous fly larvae of the family Oestridae were found. Specimens were studied in the laboratory and found to correspond to a Cuterebra species of the buccata species-group, of which their normal hosts are hares and rabbits (Lagomorpha). Their characteristics are similar to those described for Cuterebra buccata, but the level of taxonomic knowledge of the larval stage of this family does not permit a confident identification to species. The coyote scat from which the bot fly larvae were recovered indicates that damage in the digestive tract of rabbit-predators may have serious consequences in individuals, and an increment in the abundance of these flies may favor a health problem that diminishes the life quality, not only for normal hosts, but also for their predators.